Public acceptance of COVID-19 vaccines: cross-national evidence on levels and individual-level predictors using observational data - Lindholt, Marie Fly; Jørgensen, Frederik; Bor, Alexander; Petersen, Michael Bang (BMJ open, 2021)
ObjectivesThe management of the COVID-19 pandemic hinges on the approval of safe and effective vaccines but, equally importantly, on high vaccine acceptance among people. To facilitate vaccine acceptance via effective health communication, it is key to understand levels of vaccine scepticism and the demographic, psychological and political predictors. To this end, we examine the levels and predictors of acceptance of an approved COVID-19 vaccine.Design, setting and participantsWe examine the levels and predictors of acceptance of an approved COVID-19 vaccine in large online surveys from eight Western democracies that differ in terms of the severity of the pandemic and their response: Denmark, France, Germany, Hungary, Sweden, Italy, UK and USA (total N=18 231). Survey respondents were quota sampled to match the population margins on age, gender and geographical location for each country. The study was conducted from September 2020 to February 2021, allowing us to assess changes in acceptance and predictors as COVID-19 vaccine programmes were rolled out.Outcome measureThe outcome of the study is self-reported acceptance of a COVID-19 vaccine approved and recommended by health authorities.ResultsThe data reveal large variations in vaccine acceptance that ranges from 83% in Denmark to 47% in France and Hungary. Lack of vaccine acceptance is associated with lack of trust in authorities and scientists, conspiratorial thinking and a lack of concern about COVID-19.ConclusionMost national levels of vaccine acceptance fall below estimates of the required threshold for herd immunity. The results emphasise the long-term importance of building trust in preparations for health emergencies such as the current pandemic. For health communication, the results emphasise the importance of focusing on personal consequences of infections and debunking of myths to guide communication strategies.